(1)5×(-4)=(2)(-6)×4=(3)(-7)×(-1)=(4)(-5)×0=(5)(6)(7)(-3)×(8)=(9)=(10)=(11)5×(-4)=(12)(-6)×4=(13)(-7)×(-1)=(14)(-5)×0=(15)(16)(17)(-3)×(18)(+4)×(-5)=(19)(+4)×(-5);(20)(-)×(-8)=(22)(-2)×(-)=(23)0×(-)=(24)(-)×(+)=(25)(-1)×a=(26)(-6)×(+8)=(27)(-)×(-)=(28)(-2)×(-2)=(29)(-288)×0=(30)(-2)×(-)=(1)(-)×(-36)×0×(-25);(2)(3)(-6)×5×;(3)(-4)×7×(-1)×(-);(4)(5)(6)(7)(9);(10)(11)(12)(-3)×(-)×(-2)×33;(13)(-+-)×(-36).(14)(-+--)×(-20);(15)-×(12-2-)(16)(17)(+)×|-|×2×(-5);(18)(-1)×3(-)×(-1(19)(20)(21)(22)(-)××(-4)×4;(23)(-)×(-18)+(-)×(-3)×2;(24)(-)×2+(-)×(-2)+×(-7).(25)(-4)×(-)×;(26)(27)[(-2)×(-4)+(-5)]×[-3-(-2)×(-3)].(28)(29)(-)××(-2)×(-8);(30)[(4×8)×25-8]×125;(31)-100×-×+×(-%)4、运用运算律填空.(1)-2×(-3)=(-3)×(_______).(2)[(-3)×2]×(-4)=(-3)×[(______)×(______)].(3)(-5)×[(-2)+(-3)]=(-5)×(_____)+(_____)×(-3)
有理数混合运算 来自淘豆网m.daumloan.com转载请标明出处.